Historical and theoretical foundations for the use of the traditions of folk pedagogy in the training of teachers (Eurasian Scientific Herald, 2022)
Pedagogical traditions as a socio-historical wealth of peoples in the current conditions acquire a special meaning. On the one hand, the new time is called upon to revive, preserve and enrich the progressive traditions of the peoples inhabiting a particular region. On the other hand, introducing new generations of our compatriots to these values is the contribution to history that gives them stability, reliability, and continuity. Folk pedagogy, which contains the traditions of mankind reliably tested by time and historical selection, is today a subject of social demand and relevance for many ethnic groups of Uzbekistan